2004
DOI: 10.1128/jb.186.11.3590-3598.2004
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Sulfoxide Reductase A (MsrA) Deficiency Affects the Survival ofMycobacterium smegmatiswithin Macrophages

Abstract: Methionine sulfoxide reductase A (MsrA) is an antioxidant repair enzyme which reduces oxidized methionine to methionine. Since oxidation of methionine in proteins impairs their function, an absence of MsrA leads to abnormalities in different organisms, including alterations in the adherence patterns and in vivo survival of certain pathogenic bacteria. To understand the role of MsrA in intracellular survival of bacteria, we disrupted the gene encoding MsrA in Mycobacterium smegmatis through homologous recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 51 publications
1
67
0
Order By: Relevance
“…This showed that the strain persist within phagocytes during the initial hours of post-infection. Afterward, this value is gradually decreasing with the incubation period and reached 701 ± 52 UFC/well after 24 h, 387 ± 11 UFC/well after 48 h and finally 287 ± 14 UFC/well after 72 h. These results showed that M. smegmatis is unable to multiply inside macrophages, as reported in several previous works (Douglas et al, 2004;Sharbati-Tehrani et al, 2005). For the macrophages treated with the extract (Figure 1), we observed a significant decrease in the number of mycobacteria compared with mycobacterial load in untreated rat peritoneal macrophages.…”
Section: Intracellular Antimycobacterial Activity Of Ethanolic Plant supporting
confidence: 71%
“…This showed that the strain persist within phagocytes during the initial hours of post-infection. Afterward, this value is gradually decreasing with the incubation period and reached 701 ± 52 UFC/well after 24 h, 387 ± 11 UFC/well after 48 h and finally 287 ± 14 UFC/well after 72 h. These results showed that M. smegmatis is unable to multiply inside macrophages, as reported in several previous works (Douglas et al, 2004;Sharbati-Tehrani et al, 2005). For the macrophages treated with the extract (Figure 1), we observed a significant decrease in the number of mycobacteria compared with mycobacterial load in untreated rat peritoneal macrophages.…”
Section: Intracellular Antimycobacterial Activity Of Ethanolic Plant supporting
confidence: 71%
“…Mechanisms of phox targeting were investigated, and initial studies showed that live virulent MTB excluded phox complex in naive macrophages. Because the nonpathogen Mycobacterium smegmatis readily acquired phox in macrophages (43,44), this suggested that MTB is able to prevent the acquisition of phox. Separate studies in progress have indicated that MTB inhibits PKC activation in macrophages, and this effect could be overcome with IFN-␥ in macrophages (our unpublished observations).…”
Section: Figurementioning
confidence: 99%
“…The latter studies used immunostains to localize p47 phox and p67 phox proteins of the phox complex. Our own recent studies showed that phox proteins assembled around M. smegmatis phagosomes, and their assembly was enhanced on mutant phagosomes that were more susceptible to oxidants (44). We used a similar strategy to colocalize phox in and around MTB phagosomes.…”
Section: Figurementioning
confidence: 99%
“…Those studies provide strong evidence supporting the physiological importance of cyclic oxidation and reduction of Met residues. Knocking out MsrA caused increased susceptibility to oxidative stress in mice (5), yeast (6), and bacteria (7)(8)(9). Conversely, overexpressing MsrA conferred increased resistance to Drosophila (10), Saccharomyces (11), Arabidopsis (12), PC-12 cells (13), and human T cells (11).…”
mentioning
confidence: 99%